Peran Orang Tua dalam Mendampingi Anak Belajar di Rumah pada Masa Pandemi Covid-19 di SD Negeri 15 Rantau Bayur - Desti Ayukasari; Tutut Handayani; Fuaddilah Ali Sofyan (CV. Ulil Albab Corp, 2022)
This study aims to find out how the role of parents in accompanying children to study at home during the COVID-19 pandemic at SD Negeri 15 Rantau Bayur. The method used in this research is the method of observation, interviews and documentation. The intended subjects in this study were teachers, parents and third grade students of SD Negeri 15 Rantau Bayur. The approach used in this research is a qualitative approach with a case study method. The main focus of this research is the role of parents in assisting children to study at home during the COVID-19 pandemic at SD Negeri 15 Rantau Bayur.